Polyommatine blue butterflies reveal unexpected integrity of the W sex chromosome amid extensive chromosomal fragmentation linked to telomere restoration - Hospodářská, Monika; Koutecký, Petr; Koutková, Simona; Vila, Roger; Talavera, Gerard; Rindoš, Michal; Provazníková, Irena; Dalíková, Martina; Nguyen, Petr (Genome biology and evolution, 2025)
Chromosomal rearrangements act as barriers to gene flow and can thus promote speciation. In moths and butterflies (Lepidoptera), which possess holocentric chromosomes facilitating karyotype changes, chromosome fusions are more common than fissions. Yet, limited evidence suggests that when speciation involves chromosomal rearrangements, it is most often linked to fissions. Notable karyotypic variation is observed in three clades of the subfamily Polyommatinae (Lycaenidae), with chromosome numbers ranging from n = 10 to n = 225. We investigated genome sizes and karyotypes in several species of the genera Polyommatus and Lysandra with modal and derived high chromosome numbers. Our findings showed no support for polyploidy, confirming previous conclusions about karyotypic diversification via chromosome fragmentation in this butterfly family. Species with high chromosome numbers have slightly larger genomes, which indicate a potential role of repetitive sequences but contradicts the hypothesis of holocentric drive. Ends of fragmented chromosomes were healed with telomeres synthesized de novo, which were significantly larger than those of species with modal karyotype. No interstitial telomeric sequences were detected on autosomes. Internal telomeric signals on sex chromosomes, however, revealed multiple sex chromosome systems in Polyommatus (Plebicula) dorylas and Polyommatus icarus, with two karyotype races differing in sex chromosome constitution in the latter. Notably, the W chromosome resisted fragmentation, presumably due to its epigenetic silencing.
Keywords: fission; butterfly; sex chromosomes; telomere; fusion; Polyommatus